Model Hukum Campur Tangan Negara melalui Pendanaan Pemerintah dalam Transformasi Digital dan Pengelolaan Berkelanjutan Koperasi Desa/Kelurahan Merah Putih - Jeferson Kameo; Yefta Andi Kus Noegroho; Teguh Wahyono; Sylvia Setjoatmadja; Faqi Rawni Arndarnijariah (Jurnal Bina Praja, 2026)
The legal model governing the financing of a unique form of cooperative management in Indonesia under Article 33 of the 1945 Constitution requires further clarification. According to this management model, the state should remain present in and support cooperatives as pillars of the national economy. The administration of President Prabowo Subianto has developed this cooperative management model through the establishment of more than 83,000 Red-and-White Rural/Urban Village Cooperatives (Koperasi Desa/Kelurahan Merah Putih [KDKMPs]) throughout Indonesia, utilizing digital transformation to strengthen transparency, accountability, and sustainability in modern cooperative management. This study adopts a normative legal methodology supported by an empirical approach. Legislation, interview findings, focus group discussions, and materials from national seminars were collected, analyzed, and interpreted. The study finds that the KDKMP financing legal model is characterized by state intervention through the government’s direct financing of cooperatives using the state budget through state-owned banks as an implementation of constitutional economic principles concerning economic democracy and collective welfare.